2016
DOI: 10.1007/s10459-015-9664-3
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability and generalizability of patient note scores using a scoring rubric based on the USMLE Step-2 CS format

Abstract: Recent changes to the patient note (PN) format of the United States Medical Licensing Examination have challenged medical schools to improve the instruction and assessment of students taking the Step-2 clinical skills examination. The purpose of this study was to gather validity evidence regarding response process and internal structure, focusing on inter-rater reliability and generalizability, to determine whether a locally-developed PN scoring rubric and scoring guidelines could yield reproducible PN scores.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Extensive training and education were provided by the PA program faculty. Preexisting grading rubrics were used by faculty to grade the H&Ps to promote inter-rater reliability [ 10 ] ( Supplement 1 ). Inter-rater reliability was assessed by dual grading of a series of H&P papers by 2 random graders and calculating an intraclass correlation coefficient (ICC).…”
Section: Methodsmentioning
confidence: 99%
“…Extensive training and education were provided by the PA program faculty. Preexisting grading rubrics were used by faculty to grade the H&Ps to promote inter-rater reliability [ 10 ] ( Supplement 1 ). Inter-rater reliability was assessed by dual grading of a series of H&P papers by 2 random graders and calculating an intraclass correlation coefficient (ICC).…”
Section: Methodsmentioning
confidence: 99%
“…The CIS component of the GCE is measured using a 4‐point behaviourally anchored rating scale composed of 14 items (see Table for a full list of these items), rated by the SP directly after each encounter . The PN is scored by trained physician raters using a scoring rubric that refers to four tasks; a prior study of this rubric showed high inter‐rater reliability (weighted κ = 0.79) and validity evidence supporting its use …”
Section: Methodsmentioning
confidence: 99%
“…24 The PN is scored by trained physician raters using a scoring rubric that refers to four tasks; a prior study of this rubric showed high interrater reliability (weighted j = 0.79) and validity evidence supporting its use. 26…”
Section: Graduation Competency Examinationmentioning
confidence: 99%
“…Once training and calibration were completed, raters scored their assigned notes individually online over a period of about one month, using CAE LearningSpace. 13 In a separate rater analysis, 14 raters. 15 The full dataset using single ratings per note was used for this study.…”
Section: Datamentioning
confidence: 99%